Análisis de páginas web corporativas como desriptor estratégico - Juan Llopis Taverner; M. R. González Ramírez; J. L. Gascó Gascó (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2009)
This paper has as its main aim to analyse how corporate web pages can become an essential tool in order to detect trends by firms or sectors, and even a primary source for benchmarking. This technique has made it possible to identify the key issues in the strategic management of the Spanish in Ibex35. More precisely, two objectives were sought. The first one consisted in showing the way in which corporate websites make it possible to obtain direct information about the strategic variables which can define firms. As for the second objective, the methodology proposed served to describe the corporate profile of these large Spanish firms.
Keywords: 330; web pages; strategic management; corporate description; large firms; Spain